James Solomon Russell former slave, pioneering educator and Episcopal evangelist - Norman, Worth Earlwood (McFarland & Co., 2012)
"James Solomon Russell (1857-1935) rose to become one of the most prominent African American pastors in the post-Civil War South. This biography explores Solomon's life within the broader context of colonial and Virginia history and chronicles his struggles against the social, political, and religious structures of his day to secure a better future for all people"--Provided by publisher.